Heretic of Article 10 of the Dušan's Code - Stojanović, Stefan V. (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Emperor Dušan's Code, the most important legal act of medieval Serbia, is still the focus of attention of legal historians. One of the issues that has long been believed in science to be finally resolved, has been updated with the latest research. That question relates to the crime against religion provided for in Article 10 of the Dušan's Code, as well as to the notion of a heretic, the perpetrator of this crime. In addition to the legal-historical analysis of the mentioned article of the Code, as well as other articles necessery for its understanding, the author analyzes the opinions and views of other authors, and makes his arguments on the notion of heretic reffered to in Article 10 of the Dušan's Code.